The Relationship Between Human Resources Wellbeing and Organizational Success - Syafruddin Kitta; Nurhaeda Z (Al-Buhuts, 2024)
This study aims to investigate the relationship between human resources (HR) wellbeing and organizational success, focusing on dimensions such as job satisfaction, mental health, and work-life balance. A mixed-method approach combining quantitative surveys and qualitative interviews will be employed. Surveys will gauge perceptions of work-life balance, engagement, and retention among employees, while interviews will provide deeper insights into their experiences. Data analysis will involve statistical techniques for quantitative data and thematic analysis for qualitative data. The findings reveal a significant positive correlation between employee wellbeing and organizational success. Prioritizing employee wellbeing leads to higher productivity, innovation, and resilience within organizations. Supportive organizational cultures and transformational leadership play crucial roles in fostering employee wellbeing and driving organizational performance. The study's findings suggest that investing in employee wellbeing initiatives and cultivating supportive organizational cultures can yield tangible benefits for organizations, including increased productivity, employee retention, and customer satisfaction. These insights offer actionable strategies for organizational leaders and HR practitioners to enhance employee wellbeing and achieve sustainable growth and competitiveness.